Effective NaBH4-exfoliated ultrathin multilayer Co(OH)2 nanosheets arrays and sulfidation for energy storage. (16th May 2018) - Yang, Wanjun; Qu, Gan; Chen, Mingyue; Ma, Wenhao; Li, Wenhui; Tang, Yiwen
Abstract: Facile engineering ultrathin nano structural materials is still a huge challenge for material science. Thereinto, the strategy of exfoliating shows great advantages. In this work, we develop a convenient approach to exfoliate Co(OH)2 nanosheets into ultrathin Co(OH)2 nanoflakes through NaBH4 -exfoliation method. Moreover, the microstructures of the Co(OH)2 nanosheets are conveniently controlled by varying the exfoliation time. As a result, the obtained ultrathin Co(OH)2 -72 h nanosheets deliver the excellent electrochemical performance. In order to improve the energy storage properties, the obtained ultrathin Co(OH)2 nanosheets are further modified to enhance the conductivity via sulfidation. Consequently, the synthesized Co(OH)2 -72 h/CoS2 composites exhibit a specific capacitance of 2536 F g −1 at 1 A g −1, which is more outstanding than that of Co(OH)2 -72 h. What's more, the Co(OH)2 -72 h/CoS2 composites show a capacitance retention of 83.3% after 10 000 cycles. Besides, the assembled asymmetric supercapacitor displays a power density of 482 W kg −1 at an energy density of 36 Wh kg −1, demonstrating a large potential for application.